Universities students’ perspective on the use of English as a Medium of Instruction (EMI) in the classroom - P'ng, Georgina Syn Huey (2021)
English as one of the global or international language has been used for business, technology, and education. In Malaysia, English has been used as the language of instruction mainly in the higher education. This study aims to investigate the universities students’ perception on the use of English as the medium of instruction (EMI) in the classroom and to find out the challenges that the universities students’ encounter in using English as the medium of instruction (EMI) in the classroom. This research is conducted using mixed-method. The questionnaire and the interview results indicate that there are various perceptions of the students regarding EMI, in addition to difficulties linked with using EMI. The targeted population of this research is the universities undergraduate students from University Tunku Abdul Rahman (UTAR).